2016
DOI: 10.2217/nnm-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Star-Shaped Polylactide Scaffolds for Bone Regeneration Fabricated By Two-Photon Polymerization

Abstract: The SSL scaffolds provide a beneficial microenvironment for the osteogenic MSCs' differentiation in vitro and support de novo bone formation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…Scaffolds usually provide an environment for cell differentiation and survival. In bone tissue engineering, many scaffolds, such as collagen, ceramic, hydroxyapatite scaffolds, and biodegradable synthetic scaffolds including polymer scaffolds, have been developed for inducing bone regeneration [Salinas et al, 2013;Lovati et al, 2016;Timashev et al, 2016;Ye et al, 2016]. As mentioned above, atelocollagen not only acts as a scaffold, but it also promotes osteoblast differentiation and type I collagen production [Kagawa et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds usually provide an environment for cell differentiation and survival. In bone tissue engineering, many scaffolds, such as collagen, ceramic, hydroxyapatite scaffolds, and biodegradable synthetic scaffolds including polymer scaffolds, have been developed for inducing bone regeneration [Salinas et al, 2013;Lovati et al, 2016;Timashev et al, 2016;Ye et al, 2016]. As mentioned above, atelocollagen not only acts as a scaffold, but it also promotes osteoblast differentiation and type I collagen production [Kagawa et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Twostaged synthetic strategy of fabricating tetrafunctional polylactides has been presented in the work [9]. A derivative with 760 Da molecular mass of one arm (or 10.5 lactide links) was chosen for fabricating 3D structures.…”
Section: Methodsmentioning
confidence: 99%
“…The developed strategy of the synthesis of four functional polylactides allowed us to perform the reaction in two stages and to achieve a high percent of the target product yield (>90%) and narrow molecular mass distribution (M w /M n <1.2) [9]. The structure and purity of the synthesized polymer were verified by NMR spectroscopy.…”
Section: Synthesis Of Reactive Polymers and Their Structuring By Two-mentioning
confidence: 99%
See 1 more Smart Citation
“…Ficek et al in [19] demonstrated the positive results in the treatment of bone cysts using PLA. Timashev et al [20] analyzed the 3D biodegradable scaffold for bone tissue regeneration. Furthermore, the materials made of the lactic acid copolymers have been used as membranes for the GBR (guide bone regeneration), screws and pins to treat defects in bone [21][22][23].In proposed solution, the biodegradable polymer constitutes a scaffold for new osteoblasts cell.…”
Section: Introductionmentioning
confidence: 99%